Tanshinone I induces cell apoptosis by reactive oxygen species-mediated endoplasmic reticulum stress and by suppressing p53/DRAM-mediated autophagy in human hepatocellular carcinoma - Xu Liu; JiKui Liu (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Human hepatocellular carcinoma (HCC) is the most common type of liver cancer, and it has a high mortality rate. Despite surgical treatments, radiotherapy, and chemotherapy, the median survival of patients with advanced HCC is low. Evidence has shown that tanshinone (TA) I exhibits anti-proliferative activity against numerous cancers. However, the role of TA I and its mechanism in HCC remain unknown. Here, we determined the anti-cancer potential of TA I against HCC cell lines HepG2 and Huh7. Cell viability was analyzed using a Cell Counting Kit-8 assay. Flow cytometry was used to analyze cell cycles and apoptosis. Western blotting was used to detect protein expression and phosphorylation levels. TA I was found to inhibit cell proliferation, induce G0/G1 phase arrest, and trigger apoptosis in HepG2 and Huh7 cells. We further explored the molecular mechanism of TA I-mediated apoptosis. Our results showed that TA I induced G0/G1 phase arrest through downregulation of cyclin D1 expression and upregulation of p21 expression. TA I induced cell apoptosis via reactive oxygen species-mediated endoplasmic reticulum stress and by inhibiting p53/damage-regulated autophagy modulator (DRAM)-mediated autophagy in HepG2 and Huh7 cells. Therefore, TA I may be an anti-cancer drug candidate in the treatment of HCC.